Aplicación de la aceptación tácita como figura del silencio administrativo en la legislación tributaria ecuatoriana y el derecho a la seguridad jurídica - Villacrés Ramírez, Jhon Andrés (2023)
ABSTRACT: This investigative work aims to analyze, legally and doctrinally, the application of tacit acceptance as a figure of administrative silence in Ecuadorian tributary legislation and its impact on the legal certainty right. Through the critical-descriptive method, the application of organizational silence in tax matters was analyzed, understanding that the Organic Administrative Code regulates the practice of public Administration of the entities that comprise it; article 207 says that whatever request addressed to Public Administration must be solved in thirty days. Otherwise, the request will be solved positively by the administrator. On the other hand, Article 104 of the tributary code establishes tacit acceptance, which means the approval of the claim as administered's benefit because of the time, according to Article 132, it is 20 days. As is evident, the research topic lies in the temporality that the two codes conclude; the Administrative Code fulfills its role of regulating the actions between the Administration and the Administration. In its desire to protect this relation, it has created the figure of administrative silence to guarantee fundamental rights, as well as it can, and encourage public action for being diligent, fast, and safe. As part of Public Administration, taxation cannot be exempt from such a legal imperative. This investigative task aimed to identify if applying tacit acceptance violates fundamental rights such as legal certainty; there was a contrast of ideas in the results because of the different population criteria used as the investigative instrument.